Pedeset godina neuvjetovanja mišljenja - Donev, Dejan (Hrvatsko filozofsko društvo, 2008)
Anniversary is an occasion good enough to take a look at where we have arrived, and, even more importantly, to analyze the resulting consequences. Entering the philosophy at the times burdened by daily-political rules, I have noticed that the Croatian Philosophical Society is detached from the regime, and that it succeeded in its basic mission – respecting individual worldviews and stimulating the wide development thereof, so confirming its ethical foundations. Keeping this line of individual’s right to his/her worldview, by interiorizing given philosophical systems, but without being conditioned by them, the Croatian Philosophical Society plays the role of an ethical guide, which makes it a model to be followed by every philosophical association, as well as the model for how to spread one’s influence outside the scope of one’s natural environment
Fifty Years of Unconditioned Thinking
Keywords: Croatian Philosophical Society, philosophical system, ethical guidance, philosophical thinking, ethical foundation, Macedonia, unconditioned thinking